2013
DOI: 10.1111/efp.12091
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Spanish isolates of Heterobasidion annosum s. s. in Pinus pinaster seedlings

Abstract: The aim of this study was to test the pathogenicity of two Spanish isolates of Heterobasidion annosum sensu stricto in 2-year-old Pinus pinaster seedlings. Two types of inocula (woodchips and sawdust) were used to infect the seedlings by two different routes (stem inoculation and soil infestation). The mortality rates of the stem-inoculated seedlings differed significantly from controls, but those of the seedlings infected via soil infestation did not differ. For both types of inoculation, the lesions were lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The ANOVAs were carried out using the “Wilcox’ Robust Statistics (WRS)” package implemented in the R software environment. For girdling analysis, the variable was previously transformed to a quantitative variable using the area under the disease progress curve (AUDPC), calculated as the sum of the area of the corresponding trapezoids for the 37 weeks (Prieto‐Recio, Martín‐García, & Diez, ).…”
Section: Methodsmentioning
confidence: 99%
“…The ANOVAs were carried out using the “Wilcox’ Robust Statistics (WRS)” package implemented in the R software environment. For girdling analysis, the variable was previously transformed to a quantitative variable using the area under the disease progress curve (AUDPC), calculated as the sum of the area of the corresponding trapezoids for the 37 weeks (Prieto‐Recio, Martín‐García, & Diez, ).…”
Section: Methodsmentioning
confidence: 99%
“…The scale of symptoms was previously transformed to a quantitative variable using the area under the disease progress curve (AUDPC), calculated as the sum of the area of the corresponding trapezoids for the trial duration [56,57]. As the data violated two of the ANOVA assumptions (normality and homogeneity of variances), robust statistical methods were applied [58].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In the Iberian Peninsula, P. pinaster decline has been observed in different areas recently. While in some stands biotic agents can be responsible for P. pinaster decline (Prieto-Recio et al, 2014;Álvarez et al, 2015;Calvão et al, 2019), other studies found no evidence of any major biotic stress causing P. pinaster decline in central Spain, pointing to water stress and land-use legacies as the major drivers behind tree decline (Prieto-Recio et al, 2015;.…”
Section: Introductionmentioning
confidence: 94%